ANALISIS PENGARUH KARAKTERISTIK PERUSAHAAN TERHADAP PENGUNGKAPAN TANGGUNG JAWAB SOSIAL (Studi Kasus pada Perusahaan Manufaktur yang termasuk Daftar Efek Syariah Periode 2009-2010) - , Ahmad Sidi Pratomo ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The aim of this research is to examine some determinants of corporate social responsibility disclosure in Indonesian companies. The corporate social responsibility disclosure include details of the environment, energy, employee health and safety, employee other, product, community involvement and general. This research attempts to correct with used five corporate characteristics as explanatory varables. They are company size, profitability, leverage and ownership. The sample of this research was extracted with stratified random sampling method. Measurement of corporate social responsibility is based on corporate social reporting category to calculate the Corporate Social Responsibility Index (CSRI) that seen from the company's annual report. The population of this study is shariah companies listed (DES) in Indonesia Stock Exchange (ISX) in 2009 and 2010. Data analysis was performed with the classical assumption and hypothesis testing using linear regression. The results of this study indicate that company size have significant positive influence on corporate social responsibility disclosure, but profitability and leverage failed to show its significant effect.